Sustainability Reporting and Boards: Is That All About Gender? - Mara MADALENO; Daniel MAGUETA; Elisabete VIEIRA (Communications of International Proceedings, 2023)
We analyze the existent literature relating to gender diversity and sustainability reporting (SR) practices. The SCOPUS bibliographic database was used, and 49 documents were included in the analysis. The first document was published in 2011 and the most recent in 2023. Using the search criteria and analysis, policy implications have been highlighted. This article provides important findings as to future research needs and concludes that gender diversity has received growing attention. However, findings reported in the literature show opposite results. Gender diversity has been considerably explored considering SR, corporate social responsibility (CSR), environment, social and governance (ESG), and sustainable development goals (SDGs), but other forms of diversity are usually not reported by companies, neither explored empirically in the literature.
Keywords: Sustainability Reporting; Gender Diversity; Bibliographic Analysis; SCOPUS.